Revision of the Pseudagrion red-group occurring in Asia west of Lydekker’s line, with description of four new species (Odonata: Coenagrionidae) - Seehausen, Malte; Kalkman, Vincent J.; Bedjanič, Matjaž (Zootaxa, 2025)
Species belonging to the Pseudagrion red-group, defined as Pseudagrion Selys, 1876 species with a predominantly reddish colour pattern at least when immature, occurring between the Indian Andaman and Nicobar Islands in the west, and the Indonesian Maluku Islands west of Lydekker’s line in the east are revised. A characterization of both sexes, and illustrations of the males, are provided for P. buenafei Müller, 1996, P. coriaceum Selys, 1876, P. crocops Selys, 1876, P. declaratum Lieftinck, 1936 stat. nov., P. deflexum Lieftinck, 1936 stat. nov., P. enganoense Lieftinck, 1948 stat. nov., P. obscurum Lieftinck, 1936 stat. nov., P. perfuscatum Lieftinck, 1937, P. pilidorsum Brauer, 1868, P. pruinosum pruinosum (Burmeister, 1839), P. pruinosum elongatum Needham, 1930 stat. nov., P. simalurum Lieftinck, 1948 stat. nov. (Female unknown), and P. ustum Selys, 1876. Also photographs of almost all respective name-bearing type specimens are provided, except for the female P. ustum. Pseudagrion pruinosum fraseri Schmidt, 1934 syn. nov., and P. pruinosum ranauense Schmidt, 1934 syn. nov. are considered junior synonyms of P. pruinosum pruinosum. Four new species are erected and illustrated: Pseudagrion acutidens sp. nov. (holotype ♂: acq.v.1933, Tobelo, Halmahera Island, North Maluku, Indonesia, approximately 1.724°N, 127.997°E, van Diejen leg., no. 1519102; deposited at Naturalis Biodiversity Center Leiden, the Netherlands); Pseudagrion halmaherae sp. nov. (holotype ♂: 7.–12.x.1951, Biaur, Halmahera Island, North Maluku province, Indonesia, 600 m a.s.l., approximately 1.3°N, 127.7°E, no. 1519084; deposited at Naturalis Biodiversity Center Leiden, the Netherlands); Pseudagrion igneum sp. nov. (holotype ♂: 8.xii.1998, Chiriyatapu, South Andaman, India, approximately 11.503°N, 92.702°E, ex. Coll. M. Hämäläinen, Wen-Chi Yeh, no. 1152912; deposited at Naturalis Biodiversity Center Leiden, the Netherlands); and Pseudagrion nigrihumerale sp. nov. (holotype ♂: 8.i.2001, Munak, Kamorta Island, Nicobar Islands, India, approximately 8.01°N, 93.505°E, Dr Prashant Mohanraj leg., ex. Coll. M. Hämäläinen, no. 1552778; deposited at Naturalis Biodiversity Center Leiden, the Netherlands). The difficulties in identifying P. pilidorsum in Borneo are briefly discussed. Distribution maps of the 16 species and one subspecies are provided, and field photos are presented of P. acutidens, P. coriaceum, P. crocops, P. declaratum, P. deflexum, P. igneum, P. perfuscatum, P. pilidorsum, P. pruinosum pruinosum, P. pruinosum elongatum, and P. ustum.